Sustainable integrated farming system model for enhancing profitability, resource efficiency, and soil health for smallholders in the Indian Mediterranean ecosystem of the North-Western Himalayan region - Thakur, N. P.; Kachroo, Dileep; Kumar, Parshotam; Gupta, A. K.; Ravishankar, N.; Khajuria, V.; Koul, Vikas; Attri, Meenakshi; Mehta, Swati; Avila-Quezada, Graciela Dolores; Mattar, Mohamed A.; Salem, Ali (Frontiers in Sustainable Food Systems, 2025)
IntroductionIndian agriculture faces major challenges including declining profitability, shrinking landholdings, rising input costs, and soil fertility degradation, all exacerbated by climate change. Small and marginal farmers, constituting about 90% of the sector, are particularly vulnerable. Integrated Farming Systems (IFS) offer a pathway to diversified, resource-efficient, and sustainable farming. This study aimed to develop and evaluate a 1 ha IFS model under irrigated subtropical conditions of Jammu, India.Materials and MethodsA diversified IFS model was implemented comprising cereals, vegetables, fodder crops, horticultural plantations, a dairy unit, poultry–cum–fishery system, mushroom cultivation, a biogas unit, and vermicomposting. Emphasis was placed on recycling farm resources to reduce external input dependence. Productivity was measured as rice equivalent yield (REY), with economic analysis covering costs, returns, and benefit–cost ratio. Employment generation was expressed in man-days/ha. Soil samples from different zones were analyzed for organic carbon and bulk density.ResultsThe IFS achieved annual productivity of 23.55 t REY/ha and net profitability of ₹3.05 lakhs/ha, while generating 481 man-days/ha of employment. Animal-based components contributed the highest share of profit (45.5%). Recycling of resources met about 75% of on-farm input requirements, reducing external input costs by ~40%. Soil organic carbon increased significantly, and bulk density decreased, particularly in horticultural and plantation zones. The system also provided food and nutritional security for a five-member household.DiscussionThe IFS model enhanced productivity, profitability, and employment while improving soil health and reducing input dependency. Livestock enterprises were critical for economic stability, and resource recycling improved input efficiency. Diversification supported ecological sustainability and household food security, underscoring IFS as a resilient strategy for smallholder farmers in subtropical irrigated regions.